2012
DOI: 10.1515/bc-2011-227
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in Fanconi anaemia: from cells and molecules towards prospects in clinical management

Abstract: Fanconi anaemia (FA) is a genetic disease featuring bone marrow failure, proneness to malignancies, and chromosomal instability. A line of studies has related FA to oxidative stress (OS). This review attempts to evaluate the evidence for FA-associated redox abnormalities in the literature from 1981 to 2010. Among 2170 journal articles on FA evaluated, 162 related FA with OS. Early studies reported excess oxygen toxicity in FA cells that accumulated oxidative DNA damage. Prooxidant states were found in white bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 96 publications
1
40
0
Order By: Relevance
“…To explore the clinical significance of Salidroside in HSC maintenance in a disease model, we employed the Fanconi anemia (FA) mouse model, in which oxidative stress has been identified as a physiologic mediator of HSC loss (10,29,48). To this end, we treated Fanca -/ -or Fancc -/ -mice and their Fig.…”
Section: Salidroside Activates Parp1 Through Binding To the Wgr Domaimentioning
confidence: 99%
“…To explore the clinical significance of Salidroside in HSC maintenance in a disease model, we employed the Fanconi anemia (FA) mouse model, in which oxidative stress has been identified as a physiologic mediator of HSC loss (10,29,48). To this end, we treated Fanca -/ -or Fancc -/ -mice and their Fig.…”
Section: Salidroside Activates Parp1 Through Binding To the Wgr Domaimentioning
confidence: 99%
“…A biallelic mutation in any of the 16 identified FANC genes causes the rare DNA damage response (DDR) syndrome Fanconi anemia. The symptoms of this syndrome include bone marrow failure, genetic instability, a predisposition to acute myeloid leukemia and head and neck cancers (Soulier, 2011), altered free radical generation and detoxification (Pagano et al, 2012), and abnormalities in cytokine production and responses (Briot et al, 2008;Pang et al, 2001;Rosselli et al, 1992). This clinical and cellular heterogeneity could result from a general disturbance of the cell and tissue metabolism as a consequence of a DDR defect, but it might also be caused by alternative activities of a single FANC protein or the existence of other currently unidentified targets of the FANCcore complex.…”
Section: Introductionmentioning
confidence: 99%
“…Joenje et al later reported that chromosomal aberrations in FA were oxygen dependent (52). Since then, oxidative stress was found to modulate cell growth (26,90,91) and cycle in FA cells (26,(90)(91)(92)105) and linked to FA-associated chromosomal instability (26,52,68,90,91,100). Both in vitro and in vivo evidence indicated that FA cells were in a prooxidant state (1, 8, 11, 17, 18, 20-22, 26, 28, 37, 68, 69, 71-77, 87, 88, 90-92, 100, 103, 134).…”
Section: Oxidative Stress Contributes To the Fa Cellular And Clinicalmentioning
confidence: 99%
“…Moreover, in the presence of genotoxic agents, such as radiation or chemotherapeutic drugs, the cytotoxic effects of TNFa can be potentiated. Overproduction of TNF-a in FA cells enhances intracellular events such as nuclear factor-jB (NFjB) activation and transcriptional activity, and leads to constitutive activation of multiple signaling pathways, including mitogen-activated protein kinase (MAPK), NF-jB (two major stress-signaling pathways), and c-Jun NH2-terminal kinase ( JNK) pathway (26,88,90,105). Furthermore, TNF-a treatment upregulated the expression of FANCA and FANCG, and increased the FANCA/FANCG complex in the nucleus as well through the NF-jB pathway (71,72) Indeed, TNF-a and its interactors have been implicated in FA pathogenesis (26,88,90,105).…”
Section: Oxidative Stress Contributes To the Fa Cellular And Clinicalmentioning
confidence: 99%
See 1 more Smart Citation